2012
DOI: 10.1242/dev.071407
|View full text |Cite
|
Sign up to set email alerts
|

A complex choreography of cell movements shapes the vertebrate eye

Abstract: Optic cup morphogenesis (OCM) generates the basic structure of the vertebrate eye. Although it is commonly depicted as a series of epithelial sheet folding events, this does not represent an empirically supported model. Here, we combine four-dimensional imaging with custom cell tracking software and photoactivatable fluorophore labeling to determine the cellular dynamics underlying OCM in zebrafish. Although cell division contributes to growth, we find it dispensable for eye formation. OCM depends instead on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
224
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(237 citation statements)
references
References 53 publications
(80 reference statements)
13
224
0
Order By: Relevance
“…In the light of current evidence, this seems an unlikely possibility. Although cell proliferation was initially hypothesized as a cellular mechanism operating during optic cup morphogenesis 59 , more recent reports using DNA synthesis inhibitors have shown that proliferation is largely dispensable for the morphogenesis of the nervous system in Xenopus 60 and of the optic cup in zebrafish 21 . In fact, optic cup invaginates between 16 and 20 h.p.f.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the light of current evidence, this seems an unlikely possibility. Although cell proliferation was initially hypothesized as a cellular mechanism operating during optic cup morphogenesis 59 , more recent reports using DNA synthesis inhibitors have shown that proliferation is largely dispensable for the morphogenesis of the nervous system in Xenopus 60 and of the optic cup in zebrafish 21 . In fact, optic cup invaginates between 16 and 20 h.p.f.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, optic cup invaginates between 16 and 20 h.p.f. in zebrafish, a 4-h period in which only a modest increase in cell number takes place 21 . Moreover, here we show no significant correlation between retinal size and optic cup folding defects on knockdown of vsx2 in zebrafish (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of segregated placode primordia correlates in time with upregulation of transcription factors specifically expressed in individual or groups of placodes Pieper et al, 2011;Schlosser, 2010;Streit, 2008). Pax2 and Pax8, expressed in the otic and epibranchial placode progenitors (and in lateral line placodes in fish and amphibians), show saltand-pepper expression in chick (Groves and Bronner-Fraser, 2000;Streit, 2002), Xenopus (Pieper et al, 2011;Schlosser and Ahrens, 2004), zebrafish (Bhat et al, 2013;Bhat and Riley, 2011;Hans and Westerfield, 2007;McCarroll et al, 2012; Kozlowski et al, 1997;Bhattacharyya and Bronner, 2013;Breau et al, 2012;Dutta et al, 2005;Harden et al, 2012;Knaut et al, 2005;Kwan et al, 2011;Pieper et al, 2011;Streit, 2002;Whitlock and Westerfield, 2000;Xu et al, 2008) al., 2012) and mice (Ohyama and Groves, 2004). Pax6, a transcription factor expressed in the lens placode, exhibit mosaic expression in zebrafish (Dutta et al, 2005;Hans and Westerfield, 2007).…”
Section: Confrontation Of the Models With Experimental Evidencementioning
confidence: 99%